Steganography Based on Arabic Language Texts by Kashida Using STRI As RNG (Iraqi Journal of Science, 2022)
One of the primary problems in internet is security, mostly when computer utilization is increasing in all social and business areas. So, the secret communications through public and private channels are the major goal of researchers. Information hiding is one of methods to obtain a security communication medium and protecting the data during transmission.This research offers in a new method using two levels to hide, the first level is hiding by embedding and addition but the second level is hiding by injection. The first level embeds a secret message in one bit in the LSB in the FFT and the addition of one kashida. Subtraction of two random images (STRI) is RNG to find positions for hiding within the text. The second level is the injection of one or two random kashida within the text. Linguistic steganography covers all the techniques that deal with using written natural language to hide secret message. This research presents a linguistic steganography for scripts written in Arabic language, using kashida and Fast Fourier Transform on the basis of a new technique entitled subtraction of two random Images (STRI) as location to hide a secret message. The proposed approach is an attempt to present a transform linguistic steganography using levels for hiding to improve implementation of kashida, and improve the security of the secret message by using subtraction two random Images (STRI). This method was tested in terms of security and capacity, transparency, and robustness and this is way better than previous methods. The proposed algorithms ideal for steganographic properties.